Patterns of Psychedelic Use in Italy: Insights from the Global Psychedelic Survey - Beatrice Dal Bianco; Matteo Buonarroti; Alessandro Lo Jacono; Fabio Fesce; Alice Jelmoni; Lucia Cicchi; Andrea Anastasi; Eugenio Rossi; Mauro D'Alonzo; Alessandro Gelao; Caterina Bartoli; Omer Ahmed Syed; et al. (Clinical Neuropsychopharmacology and Addiction, 2026)
Background: Epidemiological data on psychedelic use in Italy is limited. In this study, Italian responders in the Global Psychedelic Survey 2025 were subanalyzed to describe patterns of use, motivations, subjective experiences, and health correlates. Methods: Adults (≥21 years) with lifetime psychedelic exposure, residing in or born in Italy or San Marino, were surveyed in a web-based, cross-sectional design. Descriptive analyses examined sociodemographics, substance use histories, motivations, intense experiences, changes in other substance use, and healthcare engagement. Results: Among 731 participants (mean age 37.4 ± 11.3 years; 59.8% male; 70.0% urban), 90.1% reported lifetime regular-dose psychedelic use, most commonly psilocybin (77.3%), MDMA (69.5%), LSD (67.0%), and ketamine (46.3%). Polysubstance exposure was common, with 83.3% reporting use of ≥2 psychedelics. Lifetime alcohol, cannabis, and nicotine use exceeded 90%, and 36.0% reported a substance-related problem. Past-year psychedelic use was reported by 76.7%, with the majority using once to a few times per year. 58.4% reported lifetime microdosing. Motivations were predominantly non-clinical. Intense experiences were often rated positive or mixed. Self-reported reductions in alcohol (45.9%) and tobacco (34.9%) were frequent. Conclusions: These findings provide the first large-scale characterization of psychedelic use patterns among a highly engaged Italian-affiliated psychedelic community. Patterns of consumption were generally intermittent, often embedded within polysubstance use contexts, and were primarily motivated by personal growth. Although many respondents reported positive experiences and reductions in other substance use, these observations require confirmation in longitudinal research.